(3GdhLjR aj JaSjQ cJGH Gddg GdYRjRs - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj GdfjSGHhQj , J (B468 (3g` s ((3eMeO Hf YHO GdQMef GdfGejS s)
(3ChdgG (B:s
(3GdMeO ddg GdcQje HBdGFg GdYXje HcHQjGFg CeG HYO aEf dcd ReGf fTQkG hdcd fTQ YdekG bhdg ef ShQI GdaGJMI s
(3BNQgG (B:s
(3jfJgi HJaSjQ ShQI GdfGS Hbhdg (B: (3jSJYjP ef TQ GdLf hef TQ GdfGS hGdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai ced cJGH GdhLjR s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs